Immune protection against reinfection with nonprimate hepacivirus - Pfänder, Stephanie; Romero-Brey, Inés; Bartenschlager, Ralf (Proceedings of the National Academy of Sciences of the United States of America, 2017)
Hepatitis C virus (HCV) displays a narrow species tropism severely hampering development of small animal models that are required for vaccine and pathogenesis studies in vivo. The recent discoveries of HCV-related hepaciviruses in diverse hosts offer new opportunities with respect to the development of an immunocompetent animal model for HCV research. Among the hepaciviruses, the equine nonprimate hepacivirus (NPHV) represents the closest homolog of HCV discovered to date. We defined key aspects of natural immunity to NPHV challenge in the cognate host and provide evidence for natural protection from NPHV infection. Further characterization of the immune signatures that confer protection against NPHV could provide important information that may facilitate the development of new prophylactic strategies including protective vaccines against HCV., Hepatitis C virus (HCV) displays a restricted host species tropism and only humans and chimpanzees are susceptible to infection. A robust immunocompetent animal model is still lacking, hampering mechanistic analysis of virus pathogenesis, immune control, and prophylactic vaccine development. The closest homolog of HCV is the equine nonprimate hepacivirus (NPHV), which shares similar features with HCV and thus represents an animal model to study hepacivirus infections in their natural hosts. We aimed to dissect equine immune responses after experimental NPHV infection and conducted challenge experiments to investigate immune protection against secondary NPHV infections. Horses were i.v. injected with NPHV containing plasma. Flow cytometric analysis was used to monitor immune cell frequencies and activation status. All infected horses became viremic after 1 or 2 wk and viremia could be detected in two horses for several weeks followed by a delayed seroconversion and viral clearance. Histopathological examinations of liver biopsies revealed mild, periportally accentuated infiltrations of lymphocytes, macrophages, and plasma cells with some horses displaying subclinical signs of hepatitis. Following viral challenge, an activation of equine immune responses was observed. Importantly, after a primary NPHV infection, horses were protected against rechallenge with the homologous as well as a distinct isolate with only minute amounts of circulating virus being detectable.